Ultrasound of the knee in rheumatology - Girish Gandikota (Indian Journal of Rheumatology)
The knee joint, surrounding ligaments, and extensor mechanism (quadriceps and patellar tendon), given their superficial nature, are easily accessible and accurately assessed with high-resolution musculoskeletal (MSK) ultrasound. Its bedside availability, lower cost than magnetic resonance imaging (MRI), and its high sensitivity in the detection of a small effusion, synovitis, and Baker's cyst, together with its ability to be used for needle guidance in invasive procedures, make ultrasound a highly desired diagnostic tool. In this article, we will focus on common rheumatologic indications of MSK ultrasound in the knee and discuss scanning technique and sonographic findings. Transducer positioning and essential sonographic bony landmarks will be reviewed and scanning in two orthogonal planes (both long and short axis of the structure) will be emphasized. With advances in technology, cost reduction, and easy availability, it is expected that more and more clinicians will be utilizing ultrasound in their clinics in management and treatment of rheumatologic diseases. The diagnostic ability of MSK ultrasound is based on an operator's training and experience, the patient's habitus and aptly chosen clinical indications. A good grasp of anatomy, sound ultrasound technique, and knowledge of limitations of ultrasound modality is essential for a safe ultrasound practice. It is also important to keep in mind that ultrasound provides limited information about internal structures such as meniscus and cruciate ligament pathologies and it has a complementary role with MRI.